2012
DOI: 10.1038/ismej.2011.211
|View full text |Cite
|
Sign up to set email alerts
|

Architectural design influences the diversity and structure of the built environment microbiome

Abstract: Buildings are complex ecosystems that house trillions of microorganisms interacting with each other, with humans and with their environment. Understanding the ecological and evolutionary processes that determine the diversity and composition of the built environment microbiome—the community of microorganisms that live indoors—is important for understanding the relationship between building design, biodiversity and human health. In this study, we used high-throughput sequencing of the bacterial 16S rRNA gene to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
453
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(498 citation statements)
references
References 56 publications
18
453
3
6
Order By: Relevance
“…Although we found a high degree of overlap in the composition of communities from Central Park and those from other biomes, there are clearly numerous taxonomic groups, which differ in abundance between Central Park and other biomes. However, one particular group that differed in relative abundance between the two sample sets were those phylotypes whose sequences were close matches to human pathogens [35,36]. While sequences matching potential human pathogens were relatively rare in all soils, humanassociated potential pathogens were over two times more abundant in the Central Park soils ( p , 0.001) (electronic supplementary material, figure S5a).…”
Section: Results and Discussion (A) Central Park Soil Diversity Is Nomentioning
confidence: 99%
See 1 more Smart Citation
“…Although we found a high degree of overlap in the composition of communities from Central Park and those from other biomes, there are clearly numerous taxonomic groups, which differ in abundance between Central Park and other biomes. However, one particular group that differed in relative abundance between the two sample sets were those phylotypes whose sequences were close matches to human pathogens [35,36]. While sequences matching potential human pathogens were relatively rare in all soils, humanassociated potential pathogens were over two times more abundant in the Central Park soils ( p , 0.001) (electronic supplementary material, figure S5a).…”
Section: Results and Discussion (A) Central Park Soil Diversity Is Nomentioning
confidence: 99%
“…We used a number of metrics to compare soil biodiversity between the Central Park and global soil sample sets. The relative abundance of potentially pathogenic bacteria was calculated following Kembel et al [35]. USEARCH [34] was conducted comparing each phylotype with a reference database of bacterial strains that are known human pathogens [36].…”
Section: (D) Comparing Central Park Soil Diversity To Global Soil DIVmentioning
confidence: 99%
“…The genera indicated were Micrococcus, Streptococcus, Corynebacterium, Propionibacterium, and Staphylococcus. 14,17,[30][31][32] Sequences classified as Micrococcus and Streptococcus were dominant in exhaust samples making up 16% and 8% of the sequences respectively. Some genera which include primary pathogenic species, such as Legionella sp., Burkholderia sp., Neisseria sp., and Mycobacterium sp.…”
Section: Bacterial Diversitymentioning
confidence: 99%
“…Our findings are supported by previous studies which found less chloroplast DNA in mechanically ventilated rooms than those with natural ventilation. 17 Mechanical ventilation systems might then be beneficial to those suffering from pollen allergies. It has been found that HVAC systems equipped with MERV13 filters, the ASHRAE equivalent to F7 filters, effectively reduced indoor levels of common asthma and allergy triggers such as cat allergens and airborne PM 2.5 .…”
Section: Bacterial Composition Of Filter Dustmentioning
confidence: 99%
“…Phyla-and class-level abundance was analyzed using analysis of variance with post-hoc Tukey's honest significant difference test. The abundance of potentially pathogenic bacteria was calculated following Kembel et al (2012) and analyzed using a t-test. Indicator family analysis was conducted with 9999 permutations using the multipatt function in indicspecies (Miquel De Caceres R).…”
Section: Statistical Analysesmentioning
confidence: 99%